A Novel Control Strategy for Hydraulic Turbines to Consider Both Primary Frequency Regulation and Ultra-Low Frequency Oscillation Suppression - Yong Jia; Bangwei Tan; Wentao Zhang; Dongrong Jiang; Chao Yang; Yunhao Wen (Energies, 2024)
In response to the requirements of mitigating ultra-low frequency oscillation (ULFO) and enhancing primary frequency regulation (PFR) performance in hydropower-dominated systems, a novel control strategy, namely the center-frequency-structured governor-side power system stabilizer (CFS_GPSS) is proposed. In this study, the transfer function model of the hydropower system with a proportional-integral-derivative (PID)-type governor is established. Through analysis of damping torque and amplitude-frequency characteristics, the dominant links and key characteristics of ULFO are revealed. Based on these findings, a CFS_GPSS strategy is proposed to compensate for the phase and increase system damping. Finally, the effectiveness of the CFS_GPSS is verified under normal operating conditions of 0.04 Hz, strong network and low hydropower output conditions of 0.034 Hz, and weak grid-connected conditions of 0.054 Hz based on the 3-machine, 9-bus system. Compared to the conventional structured governor-side power system stabilizer (CS_GPSS) control strategy and PID parameter optimization method, the CFS_GPSS demonstrates efficient ULFO suppression across a wide frequency range while significantly enhancing PFR performance. The proposed control strategy exhibited the expected performance under various operating conditions, providing effective technical means to enhance the reliability of hydraulic turbines and guide the safe and stable operation of hydropower-dominated systems.